2016
DOI: 10.1016/j.oregeorev.2015.11.016
|View full text |Cite
|
Sign up to set email alerts
|

Rare earth elements (REE)—Minerals in the Silius fluorite vein system (Sardinia, Italy)

Abstract: Rare Earth Elements (REE)-minerals in the Silius

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 36 publications
3
16
0
Order By: Relevance
“…The REE geochemistry can also be used to determine the nature and evolution of a hydrothermal fluid in fluorite deposits (Bau et al, ; Mondillo et al, ). Fluorite often shows significant variation in the REE composition in hydrothermal deposits (e.g., Schwinn & Markl, ), and the fluid composition is an important controlling factor for REE behavior (Morgunov & Bykova, ).…”
Section: Discussionmentioning
confidence: 99%
“…The REE geochemistry can also be used to determine the nature and evolution of a hydrothermal fluid in fluorite deposits (Bau et al, ; Mondillo et al, ). Fluorite often shows significant variation in the REE composition in hydrothermal deposits (e.g., Schwinn & Markl, ), and the fluid composition is an important controlling factor for REE behavior (Morgunov & Bykova, ).…”
Section: Discussionmentioning
confidence: 99%
“…Eu as an oxidation sensitive element among REE, and is strongly dependent on temperature of depositional conditions (Möller et al, 1998;Mondillo et al, 2015;Dill, 2016Dill, , 2017 Figure 6, Eu anomaly values of the samples increase from L-11 to L-15. Abedini and Calagari (2015) suggested that, both diagenetic processes and the presence of plagioclase in the limestone of the Ruteh Formation were two important factors for generation of the positive Eu anomaly.…”
Section: Lanthanide Tetrad Effect In Limestone: a Tool To Environmentmentioning
confidence: 99%
“…On the basis of field observation, silicification, brecciation, and intense shearing, this limestone has characteristically peculiar geological features. Geologic aspects, mineralogy, and petrographic features of the limestone and the enclosed bauxite ores in the Kanigorgeh district were studied in detail by Abedini and Calagari (2013c, and 2015. Calcite, quartz, plagioclase, kaolinite, and Fe-oxides (hematite) are the most abundant mineral phases in the limestone (Abedini and Calagari, 2015).…”
Section: Lanthanide Tetrad Effect In Limestone: a Tool To Environmentmentioning
confidence: 99%
“…The Y/Ho versus La/Ho diagram has been widely used to shed light on the evolution of fluorite ore formation (Bau & Dulski, 1995;Deng, Gong, et al, 2014;Mondillo et al, 2016;Pei et al, 2017). In the diagram (Figure 10a (Figure 10b) is used to differentiate the fluorite genesis (Möller et al, 1976;Sánchez et al, 2010;Sasmaz et al, 2018;Subías & Fernández-Nieto, 1995) for the Madiu deposit (Bau & Dulski, 1995).…”
Section: Samarium-neodymium Isotopesmentioning
confidence: 99%